Analisis Kerangka Media dalam Isu-Isu Politik Kontemporer - Rambe, Ahmad Sampurna; Sahlaya, Muhammad Rishan; Andini, Andini; Firdasari, Senang; Akbar, Rizky (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The media plays a central role in shaping public perceptions of contemporary political issues. Through the process of framing, the media not only conveys facts, but also determines which aspects are emphasized, obscured, or omitted. This study aims to analyze how the mass media frames current political issues and to reveal the implications of such discourse construction on public perceptions. Using a qualitative approach through literature review, this study examines academic literature on framing theory, media politics, and the dynamics of political reporting in Indonesia. The analysis reveals that media framing is significantly influenced by political interests, editorial ideology, and market pressures. Issues such as corruption, elite conflicts, or elections are often reported with biased, simplistic, and sometimes fragmented narratives. The discussion emphasizes that framing is not merely a technical editorial choice but an ideological practice that significantly shapes the socio-political reality of society. The conclusion of this study is that framing analysis needs to be developed critically as a tool to uncover biases in political news representation and as a foundation for enhancing media literacy among the public in the age of information overload.